IDENTIFIKASI TELUR NEMATODA PADA FESES TERNAK BABI DI DESA KALASEY SATU KECAMATAN MANDOLANG KABUPATEN MINAHASA PROVINSI SULAWESI UTARA - Podung, Albert J.; Paath, Jantje Ferdinand; Ponto, Juliance H.W. (Universitas Sam Ratulangi, 2020)
IDENTIFICATIOS OF NEMATODE EGGS IN PIGâ€™S FAECES IN KALASEY SATU MANDOLANG, DISTRICT OF MINAHASA OF SULAWESI UTARA PROVINCE. This study aims to determine and identify parasitic nematode worms through examination of worm eggs in pig feces. The number of worm eggs indicates the level of parasitic attack. Therefore, this study uses samples of pig manure collected from pigs in the Kalasey Satu Village, Mandolang District, Minahasa Regency. Samples will be tested using the floating method to see worm eggs. Worm egg identification was carried out in the laboratory of the Faculty of Animal Husbandry UNSRAT and analyzed descriptively and the number of worm eggs was calculated to see the level of attack on pigs. The results of this study found that from 23 pigs that had taken their faecal samples, 8 faecal samples were identified as being infected with Ascaris sp. and 1 of them was infested with Oesophagustomum sp. Three faecal samples from 3 month old pigs infected by Ascaris sp 2 samples containing Ascaris sp. and 1 sample containing Oesophagustomum sp.); 5 fecal samples of sows containing Ascaris sp. The conclusion of this study, that pigs that are in the area of Kalasey Satu Village have been infected by Ascaris sp. and Oesophagustomum sp. with a preavalence of 30,4% and 4,3%.Â Livestock conditions, feeding patterns and the environment around the cage are verry supportive of the growth and propagation of the intermediate host of endoparasites.Â Keywords: Egg, nematode, feces, pig